Desenvolvimento de personagens em pixel art para jogos digitais - Martins, João Paulo Araújo (2018)
The following work presents a proposal of a methodology of production of pixel artcharacters to be used in video games, with the intent of serving as a guide that canbe used by whomever wishes to create game characters using pixel art. The proposal was produced from a research of historical character about the usage of characters and of the pixel art technique in the video game medium, so it could be understood the importance of these areas. A further research for other less specific available methodologies was made, which were then utilized as basis for the creation of a new one, exemplified in this work by a character made using this process. Between the results reached, were developed both the methodology and the character used as an example. In the case of the character, it was done based on platforming games of the Nintendo Entertainment System console, or on a game that emulates the console limitations. As a conclusion, was observed the importance of not neglecting steps and some future work ideas that can be done using this work as a basis.